Analysis of complications associated with peripherally inserted central venous catheters. Prospective observational study - Ferraz-Torres, Marta; Diez-Revilla, Ana; Plaza-Unzue, Ruth; Corcuera-Martinez, Maria Inés (Revista Cuidarte, 2024)
Highlights • There is a need to create standardized strategies for unified vascular access care in critical patients to reduce complications. • Creating specialist teams, such as vascular access teams (VATs), allows a clear improvement in vascular access device care, reducing complications. • The prevalence of complications such as thrombosis and infection has been low. • Conducting new studies to evaluate and detect the leading causes and reasons for complications, such as accidental removal, would be advisable. Introduction: Vascular access teams often use guidelines or algorithms to determine the most appropriate vascular access device based on the patient’s condition and the substance to be infused. These guidelines are intended to help identify the most qualified personnel for device insertion, but few studies collect information on the performance of these units. Objective: This study aims to identify the evolution and complication rate of peripherally inserted central catheters (PICCs) in patients requiring vascular access. Materials and Methods: A prospective observational study was conducted over three years. Continuous variables with normal distribution were compared using Student’s t-test. Nonparametrically distributed variables were analyzed with the Mann-Whitney U test. For categorical variables, the two-tailed chi-square or Fisher’s exact test was used. Regression analysis was performed for the dependent variable of complications. Results: Of the PICCs inserted, 61.99% (566) were in patients receiving oncologic treatment, with a mean dwell time of 136±127.51 days. PICCs inserted in hematologic patients had a mean dwell time of 144±141.3 days (p=0.438). The most frequent complications were accidental removal (3.50%, 32, OR 0.581), thrombosis (3%, 27, OR 0.752), and central line-associated bloodstream infection (CLABSI) (2.10%, 19, OR, 0.113). Discussion: Complications related to PICCs were infrequent, with thrombosis being the most prevalent. Accidental removal was also frequent, a complication not thoroughly analyzed in other studies. Conclusions: PICC insertion and management by vascular access teams enables units to achieve a low complication rate in onco-hematological patients. How to cite this article: Ferraz-Torres Marta, Diez-Revilla Ana, Plaza-Unzue Ruth, Corcuera-Martinez Maria Inés. Analysis of complications associated with peripherally inserted central venous catheters. Prospective observational study. Revista Cuidarte. 2024;15(3):e3352. https://doi.org/10.15649/cuidarte.3352